نموذج المواد التعليمية للخط العربي في المدرسة الإبتدائية بمؤسسة معهد النور الكشاف الإسلامي بيكاسي - Siti Jubaidah; Maulidiana Nur Alfi Syahrin (Journal of Calligraphy, 2022)
This study aims to design a model of Arabic Calligraphy in Islamic College Foundation Elementary School El-Nur El-Kasysyaf based on a student needs analysis. This development and research uses the R&D method of R&D in the manner of Dick and Carrie model with ADDIE code. And the data collection techniques used through participatory observation, structured interview, unstructured interview and questionnaires. Arabic calligraphy material model consists of 3 themes in it, Single Letter Writing Rules, Rules for Writing Connecting Letters, Change the order of single letters to words and Otherwise. This material model also include learning books and videos as complementary material and explanation related to other write activities needed to increase innovation in increasing students interest in understanding Arabic calligraphy. The first reviewer's response for the Arabic calligraphy material model got a score of 85%, from the second reviewer got a score of 94% with the "Very Feasible" score category. The response from students reached a score of 88% in the "Very Feasible" category.